Transformation of the Romanticist Myth of the City in Alexander Pushkin’s Poem Brothers‑Robbers - Степанова, Анна (Slavia Orientalis, 2020)
The article studies the problem of the Yekaterinoslav urban text formation in Russian literature. The image of the city in the poem by Alexander Pushkin Brothers‑Robbers is analysed; the real (historical) image of Yekaterinoslav is considered in correlation with the image depicted in the poem, determined are the functions of romanticist topoi in the creation of the Yekaterinoslav text, while revealed are the peculiar features of the formation of the urban myth within the Yekaterinoslav text itself. The process of shift from the image of a real Yekaterinoslav city to the image of the ideal (non‑material) one, from a “physical” image to the “metaphysical” is investigated. There is a process of poeticizing a small city in the work of art, representing the primary stage of forming a myth about the city. After analysing the correlation of the Yekaterinoslav myth with the aesthetic constants of romanticism (the motif of freedom and predatory liberty, images of the noble robber and rebellious character, the motif of rejection, correlation with the utopian tradition) we may conclude that within the poetics of the urban text Alexander Pushkin reinterprets and transforms the traditional categories of romanticist poetics. The author’s characterization of the robber character diminishes the romantic ideal, revealing the other, “trivial” nature and interpreting rebellion not as a rejection or desire for freedom, but as a crime. Such a twist in depicting the image of a rebellious character stipulates a different interpretation of the theme of freedom, transforming it into the theme of guilt and punishment. Thus, the motifs of rejection, rebellion and repentance, compositionally uniting the development and understanding of the theme of predatory liberty in the poem, are interpreted in the metaphysical image of the city. Such a function of the city image determines the peculiar narrative structure of the poem at the level of plot, composition and style.
Keywords: Urban text; myth about a city; romanticism; Yekaterinoslav text; motif of freedom; motif of rebellion; motif of repentance